Analysis of the Impact of Online Licensing Management on the Community in Kampar Regency - Ermiwati, Ermiwati; Zulher, Zulher; Kasmawati, Kasmawati (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Online licensing management at the Kampar Regency Investment and One-Stop Integrated Services Office (DPMPTSP) to speed up and simplify the licensing process for the community. The purpose of the research was to determine the impact of online licensing management on the community. The research method is qualitative and descriptive. Data collection techniques through observation and interviews. The research source uses primary data. The results of the study show that the community faces a number of technical and non-technical obstacles and problems that cause the system to not be fully effective, such as limited internet access, low digital literacy, lack of understanding of the system, and dependence on third-party services. This study recommends an increase in technical assistance and the provision of a more equitable digital infrastructure. DPMPTSP Kampar Regency always strives to provide the best service for the community and continues to try to socialize the online system so that the public can easily understand the mechanism of managing permits through the online system.